Lexical Effects on Dichotic Word Recognition in Young and Elderly Listeners - Carter, Anne Strouse; Wilson, Richard H. (Journal of the American Academy of Audiology, 2001)
Dichotic listening was evaluated using monosyllabic word pairs that differed in lexical difficulty as defined by the Neighborhood Activation Model of spoken word recognition. Four combinations of lexically EASY and lexically HARD words were evaluated (same pair: EASY-EASY, HARD-HARD; or mixed pair: EASY-HARD, HARD-EASY) in young adult listeners with normal hearing and older adult listeners with mild-to-moderate hearing loss. The same-pair data indicated that for all subjects, EASY words were identified correctly more often than HARD words, and recognition performance on words presented to the right ear was better than performance on words presented to the left ear. Overall performance was lower and the right-ear advantage was larger for the older group. The mixed-pair data for the young group revealed that EASY words were recognized more accurately than HARD words, regardless of the ear to which they were presented. For the older adults, the words presented to the right ear were recognized more accurately than were the words presented to the left ear, regardless of the type of word. The efficiency of the processing of stimuli from the left ear is discussed as an explanation of the results for the mixed-pair conditions.Abbreviations: ANCOVA = analysis of covariance, ANOVA = analysis of variance, CV = consonant-vowel, NAM = Neighborhood Activation Model
Keywords: Aging; dichotic listening; Neighborhood Activation Model; right-ear advantage; speech perception